2022
DOI: 10.3389/fpsyg.2022.931623
|View full text |Cite
|
Sign up to set email alerts
|

The Notion of Coopetition-Based Open-Innovation in Business Practices: A Model to Accelerate Firm Performance

Abstract: In today’s competitive business market, firms that collaborate on a coopetition basis face obstacles in the form of decision-making, dependency, and trust in their competitor partners. This current study is the only one that has examined the relationship between coopetition and firm performance; yet, this relationship appears to be unclear due to the impact of trust and dependency on coopetition. This study investigates the impact of coopetition on firm performance by examining the mediating effects of decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Coopetition is important for improving the innovative performance of SMEs (Devece et al, 2019). The results have shown that firms cooperating with their competitors are likely to perform better than firms that do not use the resources and knowledge of their competitors (Avotra et al, 2022). These coopetitions involve improving existing solutions or creating new services, products, and processes and both firms share the risks and costs of innovative actions (Corbo et al, 2023).…”
Section: Coopetition Among New Technology-based Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coopetition is important for improving the innovative performance of SMEs (Devece et al, 2019). The results have shown that firms cooperating with their competitors are likely to perform better than firms that do not use the resources and knowledge of their competitors (Avotra et al, 2022). These coopetitions involve improving existing solutions or creating new services, products, and processes and both firms share the risks and costs of innovative actions (Corbo et al, 2023).…”
Section: Coopetition Among New Technology-based Firmsmentioning
confidence: 99%
“…In this framework, one can benefit from the applications of game theory for coopetition (Pujats et al, 2020) and adopt business planning strategy to improve business performance (Avotra et al, 2022). Game theory is a mathematical approach to model the decision-making process in cooperative or conflicting situations (Karabiyik et al, 2020;Lucas, 1972).…”
Section: Introductionmentioning
confidence: 99%